Water Management in Israel : Key Innovations and Lessons Learned for Water Scarce Countries - Marin, Philippe (World Bank, Washington, DC, 2017)
Despite being one of the most water scarce countries in the world, Israel has achieved water security and full cost recovery through tariffs through a series of ambitious reforms. This involved nine key innovations, namely (1) putting in place a national water conveyance system to connect all water infrastructure, (2) reuse of treated wastewater for irrigation, (3) large-scale desalination PPP for potable water independence, (4) using aquifers as reservoirs, (5) interception of surface water run-off, (6) promoting crop selectivity and importation of virtual water, (7) efficient irrigation technologies, (8) demand management and public communication, and (9) creating a supporting environment for innovation. The Israeli experience holds nine important lessons learned, which are of major importance for other countries facing increasing water scarcity: (1) building public awareness of the value of water, (2) control of water allocations, (3) access to quality data for integrated management, (4) national conveyance water system, (5) massive infrastructure investment must be done in parallel with institutional reforms, (6) low price for desalinated water depends on well-designed PPP schemes, (7) wastewater reuse is beneficial but requires subsidies, (8) corporatization of water utilities requires sound regulation and heavy-handed supervision, and (9) even in a country with large resources and strong capacity, this has been a long process and mistakes have been made.